Empfohlene Diagnostik bei Pruritus auf primär unveränderter Haut - Düll, Miriam; Kremer, Andreas (Die Dermatologie, 2024)
Background: Chronic pruritus affecting primary non-lesional skin (CPNL) manifests as a common symptom across a spectrum of diseases spanning various medical specialties. Given the diverse etiological factors involved, diagnosing the underlying condition poses a significant challenge. Objectives: To provide a comprehensive overview of clinical, laboratory, and imaging diagnostics for CPNL. Materials and methods: A thorough literature search on the diagnostics of chronic pruritus was conducted using PubMed with specific keywords “chronic pruritus AND non-lesional skin”, “chronic itch AND non-lesional skin”, “chronic pruritus AND diagnostics”, “chronic itch AND diagnostics”, “CKD-aP”, “hepatic pruritus”, “cholestatic pruritus”, and “myeloproliferative neoplasms AND pruritus”. Results: A systematic diagnostic approach is recommended for patients with CPNL, guided by the prevalence of pruritus-associated diseases. Initial basic diagnostics facilitate a cost-effective and focused evaluation during the initial medical assessment. Information pertaining to underlying diseases can be further refined through specialized diagnostic procedures. Conclusions: CPNL often presents a diagnostic dilemma. Adopting a stepwise diagnostic strategy facilitates the identification of underlying etiologies, which is crucial for recognizing diseases and administering pruritus-specific pharmacotherapy.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Basic diagnostic workup; Itch; Liver; Myeloproliferative neoplasms; Stepwise diagnostic strategy